Cost‐Effectiveness of Tramadol and Oxycodone in the Treatment of Knee Osteoarthritis. Issue 2 (31st December 2016) - Smith, Savannah R.; Katz, Jeffrey N.; Collins, Jamie E.; Solomon, Daniel H.; Jordan, Joanne M.; Suter, Lisa G.; Yelin, Edward H.; David Paltiel, A.; Losina, Elena
Abstract : Objective: To evaluate the cost‐effectiveness of incorporating tramadol or oxycodone into knee osteoarthritis (OA) treatment. Methods: We used the Osteoarthritis Policy Model to evaluate long‐term clinical and economic outcomes of knee OA patients with a mean age of 60 years with persistent pain despite conservative treatment. We evaluated 3 strategies: opioid‐sparing (OS), tramadol (T), and tramadol followed by oxycodone (T+O). We obtained estimates of pain reduction and toxicity from published literature and annual costs for tramadol ($600) and oxycodone ($2, 300) from Red Book Online. Based on published data, in the base case, we assumed a 10% reduction in total knee arthroplasty (TKA) effectiveness in opioid‐based strategies. Outcomes included quality‐adjusted life years (QALYs), lifetime cost, and incremental cost‐effectiveness ratios (ICERs) and were discounted at 3% per year. Results: In the base case, T and T+O strategies delayed TKA by 7 and 9 years, respectively, and led to reduction in TKA utilization by 4% and 10%, respectively. Both opioid‐based strategies increased cost and decreased QALYs compared to the OS strategy. Tramadol's ICER was highly sensitive to its effect on TKA outcomes. Reduction in TKA effectiveness by 5% (compared to base case 10%) resulted in an ICER for the T strategy of $110, 600 per QALY; with no reduction in TKA effectiveness, the ICER was $26, 900 per QALY. When TKA was not considered a treatment option, the ICER for T was $39, 600 per QALY. Conclusion: Opioids do not appear to be cost‐effective in OA patients without comorbidities, principally because of their negative impact on pain relief after TKA. The influence of opioids on TKA outcomes should be a research priority.